2018
DOI: 10.1016/j.redox.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

A glutaredoxin in the mitochondrial intermembrane space has stage-specific functions in the thermo-tolerance and proliferation of African trypanosomes

Abstract: Trypanosoma brucei glutaredoxin 2 (Grx2) is a dithiol glutaredoxin that is specifically located in the mitochondrial intermembrane space. Bloodstream form parasites lacking Grx2 or both, Grx2 and the cytosolic Grx1, are viable in vitro and infectious to mice suggesting that neither oxidoreductase is needed for survival or infectivity to mammals. A 37 °C to 39 °C shift changes the cellular redox milieu of bloodstream cells to more oxidizing conditions and induces a significantly stronger growth arrest in wildty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…These include glycerol kinase, hexokinase, triose phosphate isomerase, ribokinase, phosphoenol pyruvate carboxy kinase, and fumarate reductase (Table 1). Glutaredoxin, which is a redox-regulatory protein in the mitochondrial IMS and cytosol (39), was upregulated about 2-fold in TbTim50 knockdown cells (Table 1). Among the downregulated proteins, we found a number of chaperone proteins, like Hsp70 (both mitochondrial and cytosolic), DNAj, glucose-regulated protein 78 (GRP78), cyclophilin, and calreticulin (Table 2 and Data Set S1).…”
Section: Resultsmentioning
confidence: 99%
“…These include glycerol kinase, hexokinase, triose phosphate isomerase, ribokinase, phosphoenol pyruvate carboxy kinase, and fumarate reductase (Table 1). Glutaredoxin, which is a redox-regulatory protein in the mitochondrial IMS and cytosol (39), was upregulated about 2-fold in TbTim50 knockdown cells (Table 1). Among the downregulated proteins, we found a number of chaperone proteins, like Hsp70 (both mitochondrial and cytosolic), DNAj, glucose-regulated protein 78 (GRP78), cyclophilin, and calreticulin (Table 2 and Data Set S1).…”
Section: Resultsmentioning
confidence: 99%
“…1A ), a CA(Y/F)S active site sequence and a C-terminal GG motif that lacks the Cys residue 8 , 18 . Reverse genetic experiments conducted on Trypanosoma brucei ( Tb ) have shown that 1CGrx1 is the only Grx indispensable for the clinically relevant form of the parasite 8 , 19 21 and its function is linked to FeS cluster biogenesis 8 , 22 . The long N-terminal extension conserved among Kinetoplastids has been proposed to promote the non-covalent dimerization of the Grx domain 8 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in various physiological processes, such as transport of Fe-S clusters, apoptosis, DNA synthesis, cell proliferation, cell signal transduction, and immune defense ( Lillig et al, 2008 ; Allen and Mieyal, 2012 ). However, only a few Grxs from parasites have been reported, mainly on trypanosomes and Plasmodium ( Mohring et al, 2017 ; Ebersoll et al, 2018 ). This study characterized two N. caninum Grxs and explained the role of Grx1 in oxidative stress and parasite growth.…”
Section: Discussionmentioning
confidence: 99%
“…In the bloodstream stage, TbGrx2 is not essential in vitro or in vivo , but under fever-like conditions in the mammalian host, TbGrx2 deficiency leads to an increase in thermotolerance. In the procyclical stage, TbGrx2 deficiency significantly affects the morphology of the parasite and leads to irreversible proliferation arrest ( Ebersoll et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%